2018
DOI: 10.3233/jad-180297
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Amyloid Accumulation in the Aging Brain

Abstract: Background: Recent studies show links between metabolic syndrome and Alzheimer’s disease (AD) neuropathology. Understanding the link between vascular-related health conditions and dementia will help target at risk populations and inform clinical strategies for early detection and prevention of AD. Objective: To determine whether metabolic syndrome is associated with global cerebral amyloid-β (Aβ) positivity and longitudinal Aβ accumulation. Methods: Prospective study of 165 participants who underwent (11)C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 64 publications
2
23
0
1
Order By: Relevance
“…Disparity of our results from previous studies could stem from our slightly modified definition of MetS, the cross-sectional study design, the surgical nature of our sample, and the high prevalence of MetS (35.6%) compared with those studies (12.9% [30]; 15.8% [29]; 22.4% [7]) but is in line with a recent systematic review of 25 studies which concluded that the evidence on associations of MetS with cognitive impairment in older age is insufficient at present [49]. A recent report of accumulation of beta amyloid in the brains of people with MetS [50] demonstrate the need for further research into the cognitive and neuropathological consequences of the syndrome.…”
Section: Discussionsupporting
confidence: 62%
“…Disparity of our results from previous studies could stem from our slightly modified definition of MetS, the cross-sectional study design, the surgical nature of our sample, and the high prevalence of MetS (35.6%) compared with those studies (12.9% [30]; 15.8% [29]; 22.4% [7]) but is in line with a recent systematic review of 25 studies which concluded that the evidence on associations of MetS with cognitive impairment in older age is insufficient at present [49]. A recent report of accumulation of beta amyloid in the brains of people with MetS [50] demonstrate the need for further research into the cognitive and neuropathological consequences of the syndrome.…”
Section: Discussionsupporting
confidence: 62%
“…Our understanding of AD is evolving from a “brain-only disease” to a “metabolic-cognitive syndrome” 9 - 12 , 55 , 56 . AD is even referred to as “type 3 diabetes”, and a growing body of evidence suggests that abnormal brain energy metabolism is one of the main risk factors in the development of AD 12 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, patients with metabolic syndrome had an 11.48 times more likeliness to develop AD compared to those without metabolic syndrome, and there was no association between metabolic syndrome and VD. In a previous study, metabolic syndrome was associated with accelerated amyloid beta accumulation in the elderly with amyloid deposition [42]. Therefore, the combination of amyloid deposition and vascular risk factors might have increased AD incidence in individuals with metabolic syndrome.…”
Section: Discussionmentioning
confidence: 87%